Filogenia integrada de Peromyscus furvus con caracteres morfométricos y moleculares - Cruz Gómez, Alejandro (Universidad Autónoma Metropolitana, 2018)
The monotypic status of Peromyscus furvus, an endemic species of deer mouse in Mexico, which includes P. latirostris and P. angustirostris in synonymy, is analyzed throughout its geographical range, along the Sierra Madre Oriental, the Mexican Transvolcanic Belt, and the Sierra Norte of Oaxaca, by using molecular (mitochondrial gene sequences of Cytochrome-b, ND3-ND4L-ND4), size (18 linear measurements of skull and five centroid sizes), and shape (five cranioventral morphogeometric configurations) characters. The respective simple gene phylogenies, together with genetic diversity and distance analyses, as well as haplotype networks, corroborated the genetic identity of five discrete geographic groups within P. furvus. Likewise, the respective simple phylogenies for cranial size and shape, allowed to test the behavior of continuous data without or with transformations to discretize them, and validated them as systematic characters, unveiling their corresponding evolutionary patterns. By integrating the characters by type (all genes; size and shape) or as a whole (all characters) in multicharacter phylogenies, it was confirmed that P. furvus should be considered sensu lato. In brief: a) P. latirostris (San Luís Potosí and Querétaro) resumes its level as a species. P. furvus becomes polytypic with P. f. angustirostris in Hidalgo, Puebla and Veracruz, as well as with P. f. furvus in Xalapa and its surroundings, Veracruz; c) a species novo from Puerto de la Soledad, Oaxaca is discovered; d) the situation, as a species, of the populations from La Esperanza, Oaxaca, remains pending. The habitats of all these species, which constitute and clarify the situation of the furvus Group within the Genus Peromyscus, corroborates their identity and allow to update their conservation status.; Se analiza la monotipia de Peromyscus furvus, especie de ratón ciervo endémica de México que incluye en sinonimia a P. latirostris y a P. angustirostris, a todo lo largo de su ámbito geográfico en la Sierra Madre Oriental, la Faja Transvolcánica Mexicana y la Sierra Norte de Oaxaca, a partir de diferentes tipos de caracteres (moleculares: genes mitocondriales Citocromo-b, ND3-ND4L-ND4; de tamaño: 18 medidas lineales del cráneo y cinco tamaños de centroide; de forma: cinco caracteres morfogeométricos cráneoventrales). Las respectivas filogenias simples con caracteres moleculares, junto con análisis de diversidad y distancias genéticas, así como de redes de haplotipos, corroboraron la identidad genética de cinco grupos geográficos discretos dentro de P. furvus. Asimismo, las respectivas filogenias simples para el tamaño y forma craneales, probaron el comportamiento de datos continuos sin o con transformaciones para discretizarlos y validaron estos caracteres, descubriendo sus respectivos patrones evolutivos. Al integrar los caracteres por tipo (todos los genes; tamaño y forma) o en conjunto (todos) en filogenias multicarácter, se confirmó que P. furvus debía ser considerada sensu lato. En breve: a) P. latirostris en San Luís Potosí y Querétaro, retoma su nivel como especie; b) P. furvus es politípica con P. f. angustirostris en Hidalgo, Puebla y Veracruz, así como con P. f. furvus en Xalapa y sus alrededores, Veracruz; c) se descubre una species novo de Puerto de la Soledad, Oaxaca; d) queda pendiente la situación como especie de las poblaciones de La Esperanza, Oaxaca. El hábitat de todas estas especies, que constituyen y aclaran la situación del Grupo furvus dentro del Género Peromyscus, corrobora su identidad y permite actualizar su estado de conservación.